Comércio e meio ambiente: os atuais desafios das pequenas empresas frutícolas do Vale do São Patrício GO no mercado internacional - ANJOS, Diana Marques dos (2010)
The world market of fruits is in great expansion, mainly due to, among others factors, the changes in the habits of the consumption and the new technologies that improved in the production and storage of fruits. However the technical barriers are the serious obstacles for producers to get access to international markets. The State of Goiás still has a little expressive production in relation to other States, as for example, Bahia. However it has favorable climatic and soil conditions to modify this situation. The purpose of this study is to analyze the challenges of the small fruit producers in the international trade and has as focus the producer of fruits of the region of the Vale do São Patrício in Goiás. For the development of the subject commerce and environment: the current challenges of the small fruit producer companies of the Vale do São Patrício in the international market , had been used exploratory research, literature review, organizational diagnosis field, research through interview and questionnaire with presidents of the cooperatives located in the cities of Uruana, Jaraguá and Itapuranga, which represent great part of the cities of the Vale do São Patrício. The conclusion of the study allows to certify that the small producers of fruits of the region work with the product as form of alternatives for income improvement and are considerably willing to adopt improvements in the productive process and the internal and external qualities of the product, being able to acquire the environmental certification and, in such a way, to increase the commercialization of its products in the domestic and international market.